Corrosion inspection method of steam generator tubes using acoustic emission technique. (May 2015) - Hou, S.; Luo, J.; Shen, T.; Xu, J.
Abstract : Acoustic emission technique has been applied as the real-time and non-destructive inspection of corrosion on steam generator tubes. The corrosion signals gathered about steam generator tubes in service have been analysed. The detailed analysis reveals that the crack development of the heat transfer tubes has three stages. The results show that the accuracy of this method is comparable to the one of microscope examination.